2007
DOI: 10.1016/j.jtcvs.2007.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of an epidural cooling catheter with a closed countercurrent lumen to protect against ischemic spinal cord injury in pigs

Abstract: By cooling the spinal cord selectively and continuously, the newly designed epidural cooling catheter prevented ischemic injury in a pig model of aortic crossclamping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…In 1986, Robertson et al showed that moderate hypothermia (338C) increased the duration of ischemia required to produce neurological deficits in rabbits (Robertson et al, 1986). Hypothermia has been found to improve outcome in several animal models of ischemic SCI, including pigs (Colon et al, 1987;Strauch et al, 2004), rabbits (Naslund et al, 1992;Wakamatsu et al, 1999;Tetik et al, 2002), and dogs (Berguer et al, 1992;Tabayashi et al, 1993) Various new methodologies producing local cooling including epidural cooling techniques have also provided positive results (Yoshitake et al, 2007). In a study by Malatova et al (1995), an epidural cooling technique provided evidence that deep spinal cord hypothermia provided some degree of protection following a regional ischemic insult.…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…In 1986, Robertson et al showed that moderate hypothermia (338C) increased the duration of ischemia required to produce neurological deficits in rabbits (Robertson et al, 1986). Hypothermia has been found to improve outcome in several animal models of ischemic SCI, including pigs (Colon et al, 1987;Strauch et al, 2004), rabbits (Naslund et al, 1992;Wakamatsu et al, 1999;Tetik et al, 2002), and dogs (Berguer et al, 1992;Tabayashi et al, 1993) Various new methodologies producing local cooling including epidural cooling techniques have also provided positive results (Yoshitake et al, 2007). In a study by Malatova et al (1995), an epidural cooling technique provided evidence that deep spinal cord hypothermia provided some degree of protection following a regional ischemic insult.…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…In a group of studies using a closed hypothermic system in pigs, Mori et al 16 used a closed-loop catheter system to circulate iced saline in the epidural space to achieve subarachnoid cooling as low as 27.9°C. Yoshitake et al, 17 from the same institution as Mori et al, repeated a trial with that system in pigs to circulate hypothermic saline at 4°C, achieving subarachnoid temperatures as low as 20.8°C at L4, though both groups performed a partial laminectomy and ligamentum flavum removal to allow entry of their catheter system. In another study from that group, Ishikawa et al 18 showed decreased reactive hyperperfusion following aortic unclamping and postulated induction of nitric oxide synthase as a protective mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural cooling also has some drawbacks, including a sharp rise in the CSF pressure and uncertain homogenous cooling of the spinal cord. Recently, as a solution for these adverse phenomena, a countercurrent closed-lumen epidural catheter was developed [79,80].…”
Section: Spinal Cord Protection During Aortic Surgerymentioning
confidence: 99%